An illustrated summary of the prosomeric model - Puelles, Luis (Frontiers in Mammal Science, 2024)
This review summarizes and illustrates the assumptions, structure, and updates that apply to the prosomeric model of brain development. The anteroposterior structure is summarized in terms of tagmata, proneuromeres, and neuromeres. The primary dorsoventral structure relates to the four longitudinal zones of His: the floor, basal, alar, and roof plates. There exists a secondary microzonation of these primary longitudinal zones, and the alar plate domains of the neuromeres seem to show in some cases an anteroposterior tripartition. Topological consideration of the axial bending of the brain and practical consequences as regards section planes is presented. The midline, a fundamental reference, is described in detail in terms of floor, roof, and acroterminal components and landmarks. Finally, the relationship of axonal tracts and blood vessels to the subdivisions in the model is briefly treated.